Simulation of heating uniformity in a heating block system modified for controlled atmosphere treatments. (January 2016) - Yan, Rongjun; Huang, Zhi; Zhu, Hankun; Johnson, Judy A.; Wang, Shaojin
Abstract: Reliable and repeatable insect thermal mortality data rely on the performance of a heating device. Computer simulation has been widely used to optimize structures, design parameters and process conditions. To improve the temperature uniformity of a heating block system (HBS), a computer model was developed using finite element software COMSOL. Good agreement was obtained between the simulated and experimental block surface temperatures at three positions of the HBS and three heating rates. The validated computer model was further used to predict the effects of heating rates, the position of test insects and the addition of gases on the block and air temperature distributions. Simulation results showed that increasing heating rate reduced heating uniformity. The position of test insects in the treatment chamber largely affected their heating rate, with a position closer to the surface of the heat block providing a better temperature match between test insects and the HBS. When gas was added, block temperatures within the treatment chamber, particularly near the gas inlet, were influenced by gas speeds, temperatures and the gas channel design. The heating uniformity in the treatment chamber of the HBS was improved by heating the gas before adding it to the HBS, by routing the gas channel through the heating block to preheat the gas, and by using a relatively slow gas speed. The simulation results demonstrated that the validated computer model could be a reliable tool to evaluate the heating performance of the HBS for studying insect thermal death kinetics and optimize treatment conditions for the HBS when modified to include controlled atmospheres. Highlights: A computer model for CA-HBS was developed using finite element COMSOL. Validated model was effectively used to predict the HBS temperature patterns. Preheating gas with slow heating rates and gas speeds improved heating uniformity. Optimized parameters in CA-HBS could be used to evaluate insect thermotolerance.